2015
DOI: 10.1016/j.kjms.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Buffered l‐ascorbic acid, alone or bound to KMUP‐1 or sildenafil, reduces vascular endothelium growth factor and restores endothelium nitric oxide synthase in hypoxic pulmonary artery

Abstract: Ascorbic acid bound to KMUP-1 and sildenafil were examined for their antioxidant effects on vascular endothelium growth factor (VEGF) and endothelium nitric oxide synthase (eNOS) in hypoxic pulmonary artery (PA). Inhaled KMUP-1 and oral sildenafil released NO from eNOS. The effect of buffered l-ascorbic acid, alone and bound to KMUP-1 or sildenafil, for treating pulmonary arterial hypertension (PAH) is unclear. In this study, the antioxidant capacity of ascorbic acid increased the beneficial effects of KMUP-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Our previous studies have shown that KMUP‐1 can exert beneficial effects on various diseases associated with vascular dysfunction . In addition, KMUP‐1 was shown to have protective effects against the hypoxia‐induced injury in pulmonary artery and hepatic tissues. The present study demonstrated for the first time the protective effects of KMUP‐1 on EPCs under hypoxic condition.…”
Section: Discussionsupporting
confidence: 65%
“…Our previous studies have shown that KMUP‐1 can exert beneficial effects on various diseases associated with vascular dysfunction . In addition, KMUP‐1 was shown to have protective effects against the hypoxia‐induced injury in pulmonary artery and hepatic tissues. The present study demonstrated for the first time the protective effects of KMUP‐1 on EPCs under hypoxic condition.…”
Section: Discussionsupporting
confidence: 65%
“…Ascorbic acid may reverse impaired endothelium-dependent NO-mediated vasodilation in several conditions, including acute hyperglycemia and chronic renal failure [ 45 , 117 ]. The main mechanisms of NO increase include reduced NO degradation by free radicals considering ascorbic acid, as an extremely potent free radical scavenger, increase of endothelial NO synthase activity, increase in the intracellular content of tetrahydrobiopterin, reduced insulin resistance, or smooth muscle sensitivity to NO [ 45 , 46 , 116 , 118 , 119 ]. Diabetes mellitus is associated with endothelial dysfunction due to several factors, including hyperglycemia, insulin resistance, hyperlipidemia, oxidized LDL and ascorbic acid deficiency (due to an impaired vitamin C recycling), and arterial stiffness [ 46 ].…”
Section: Vitamin Cmentioning
confidence: 99%